Inventory of weather and climate related information extracted from the Hudson’s Bay Company post journals of Stupart Bay (Kangiqsujuaq) and Port Burwell (Killiniq) ... : Inventaire des informations météorologiques et climatiques extraites des journaux de poste de traite de la Compagnie de la baie d'Hudson, Stupart Bay (Kangiqsujuaq) et Port Burwell (Killiniq) ... - Ouellet-Bernier, Marie-Michèle; Brassard, Laura; Bhiry, Najat (Nordicana D, 2024)
Information related to weather, climate, sea-ice and environmental conditions were compiled from two Hudson's Bay Company (HBC) post journals. Daily information is available. Temperature, wind, cloudiness, precipitations, description of sea-ice, migration birds and other exceptional events were extracted from the post journals. Original documents were digitalized and are available in the Archives of Manitoba (Stupart Bay = B.484; Port Burwell = B.466). Stupart Bay post, now Kangiqsujuaq, was in operation from 1914 to 1940. Port Burwell post, now Killiniq, was in operation from 1920 to 1939. Several HBC employees contributed to the post journals writing. They were following a method established by the institution which ensured a uniformity in the observations. No information was found regarding the specific layout of the meteorological instruments at the Stupart Bay and Port Burwell posts. However, Ball (1994) described the observation material from an other HBC post. A picture from the Robert Bell collection ... : Les informations en lien avec la météo, le climat, l'observation des glaces ou de l'environnement ont été compilées à partir des journaux de postes de traite de la Compagnie de la baie d'Hudson (CBH). L'information est entrée sur une base quotidienne. La température, le vent, la nébulosité, les précipitations, l'état des glaces, les migrations des animaux et autres événements exceptionnels ont été extraits des journaux. Les journaux originaux sont disponibles en version numérique sur la base de données des archives du Manitoba (Stupart Bay = B.484; Port Burwell = B.466). Le poste de Stupart Bay, maintenant Kangiqsujuaq, était en activité de 1914 à 1940. Le poste de Port Burwell, maintenant Killiniq, était en activité de 1920 à 1939. Plusieurs employés de la CBH ont contribué à l'écriture des journaux des postes de traite. Ils suivaient une méthodologie établie par l'institution, ce qui permet une uniformité des observations. Aucune information précise n'est donnée sur la disposition des instruments ...